Application of PET to the Diagnosis, Staging, and Treatment of Locally Advanced Non-small Cell Lung Cancer - Li, Fei; Landis, Mark (Current Medical Imaging, 2015)
The strength of positron emission tomography (PET) lies in the application of its underlying technological and molecular biology advancements to clinical practice and pharmacological development. Currently, PET is used to identify malignant pulmonary nodules, evaluate mediastinal disease, detect distant metastasis, assess response to therapy, and identify novel oncologic drug targets. Over the last decade, PET has also increasingly influenced the management of locally advanced nonsmall cell lung cancer (NSCLC) by directing chemoradiation and surgical treatment. Although the majority of clinical trials and practice have used 2-18F- fluoro-2-deoxy-D-glucose (FDG) as the radiopharmaceutical agent for evaluating NSCLC, novel radiolabeled tracers, radiopharmaceutical agents, and targeted immunotherapy drugs are actively being investigated to improve the treatment of NSCLC. This review focuses on the utility of PET for diagnosing malignant pulmonary nodules, staging the extent of disease, and evaluating immuno-oncology therapies in locally advanced NSCLC.
Keywords: Drug development